Effects of cellulase enzyme and a bacterial feed additive on the nutritional value of sorghum grain for finishing pigs - I H Kim; C R Risley; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1993)
One hundred and twenty-eight finishing pigs (113 lb average initial body wt) were used to determine the effects of adding cellulase enzyme and Bacillus bacteria to sorghum-based diets on growth performance, carcass merit, and nutrient digestibility in finishing pigs. Treatments were: 1) corn-soybean meal-based positive control; 2) sorghum-soybean meal-based negative control; 3) Diet 2 with cellulase; and 4) Diet 2 with a bacterial feed additive (i.e., a mixture of Bacillus licheniformis, Bacillus subtilis, and Bacillus pumilus). There was a trend for greater average daily gain in pigs fed corn vs the sorghum treatments from d 0 to 28, but there was no effect of treatment on overall average daily gain (i.e., d 0 to 63). Overall feed consumption was not affected by treatment, but pigs fed the corn-based diet had 3% greater efficiency of gain compared to pigs fed the sorghum diets. Dressing percentage was not affected by treatment, but there was a trend for fat thickness at the last rib to be greater for pigs fed corn vs the sorghum treatments. Pigs fed corn had greater apparent digestibilities of dry matter, nitrogen, and gross energy than pigs fed the sorghum treatments. In conclusion, pigs fed the cornbased control diet had greater growth performance but tended to be fatter than pigs fed sorghum. Adding cellulase and the bacterial feed additive did not affect growth performance, carcass merit, or nutrient utilization in finishing pigs.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Bacili; Enzyme; Performance; Digestibility; Carcass; Finishing